Peningkatan Teacher Responsivity Melalui Integrasi Nilai Hadis Dan Teori Pianta - Jupita; Sulipah; Honipah; Istiana, Ana; Hasanah, Mawaddatul (Universitas Islam Indonesia, 2026)
The phenomenon of low teacher responsiveness, or teachers who are insufficiently responsive to students’ needs, represents a significant challenge in contemporary education, as it can hinder emotional support, cognitive development, and learning engagement. On the other hand, pedagogical values embedded in the Prophetic Hadith provide a relational foundation that emphasizes gentleness, responsiveness, and compassionate educational bonds, while the Teacher–Student Relationship theory proposed by Robert C. Pianta highlights that the quality of teacher–student relationships serves as a primary predictor of both academic and socio-emotional success. This study aims to formulate a conceptual framework for enhancing teacher responsiveness through the integration of these two perspectives. A qualitative approach employing content analysis is used to examine Hadith texts containing relational values, as well as the core literature of Pianta’s theory, in order to identify conceptual intersections. The findings reveal a strong alignment between the pedagogical principles of the Prophetic Hadith and Pianta’s relational dimensions, particularly in aspects of emotional sensitivity, responsiveness, and the development of positive relationships. This integration produces a model of teacher responsiveness that is preventive, adaptive, and value-based, while also offering a novel conceptual contribution that bridges the legacy of Islamic education with modern relational theory.